The Relationship between Yo-yo Intermittent Recovery Test Level I and Anaerobic Based Tests in Young Soccer Players - (:unkn) unknown (INT JOURNAL APPLIED EXERCISE PHYSIOLOGY, 2020)
The purpose of this study was to invastigate the relationship between Yo-Yo Intermittent Recovery Level I (YYIRI) test and commonly used Anaerobic tests such as; Sargent Jump (SJ), Standing Broad Jump (SBJ) and Hexagon Agility Tests (HAT) also refered as physical ability or athletic ability tests. A total of 20 male young soccer players (ages 14 +/- 0.0 years) voluntarily participated in the study. Tests were conducted on two consecutive days. YYIRI test total running distance was averaged at 1454 +/- 420 m. Peak Anaerobic Power (PAP) was calculated using SJ scores (2966.83 +/- 621.71 watt). Spearman's correlation test revealed that there was a significant negative correlation between HAT and YYIR1 tests (r=-0.742, p=0.000). There was no significant correlation between leg power indicator tests (SJ & SBJ) and YYIR1. In conclusion, YYIR1 test which measures Aerobic Endurance Capacity was correlated only with Hexagon Agility Test.
Keywords: Soccer; Yoyo Test; Hexagon Agility Test; Sargent Jump Test; FOOTBALL PLAYERS; PERFORMANCE; RELIABILITY; PHYSIOLOGY; FITNESS